Dark Continents Psychoanalysis and colonialism - Khanna, Ranjana (Durham, London : Duke University Press, 2003)
Introduction : worlding psychoanalysis
I - Genealogies
Psychoanalysis and archaeology
Freud in the sacred grove
II - Colonial rescriptings
War, decolonization, psychoanalysis
Colonial melancholy
III - Haunting and the future
The ethical ambiguities of transnational feminism
Hamlet in the colonial archive
Coda : the lament
Notes bibliogr., index
0013